2017
DOI: 10.1155/2017/2105012
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Rural People’s Basic Needs and Forest Products: A Case Study of the Katha District of Myanmar

Abstract: The understanding of interaction between rural people and forest products is one of the challenges faced while balancing forest product utilization with forest conservation in Myanmar. This study aims to contribute an effort to such challenges by analyzing the interaction of rural households with forest products in Myanmar. Data were collected using face-to-face questionnaire interviews with 218 households and conducting a rapid tree inventory across 132 circular random plots in selected rural communities arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 35 publications
3
40
3
Order By: Relevance
“…However, there was need for government intervention in strengthening institutions that cushioned the farmers in the form of land tenure, contractual issues and the provision of long lasting infrastructure besides the operational finance provided by the private contracting firms [23]. In Nepal, studies have shown that community participation in forestry programs has yielded an increase in forest product output and better forest outlook, but there is dearth of studies on the financial returns of such participation at the household level [20,47].…”
Section: Smallholder Tobacco Production As a Livelihood Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…However, there was need for government intervention in strengthening institutions that cushioned the farmers in the form of land tenure, contractual issues and the provision of long lasting infrastructure besides the operational finance provided by the private contracting firms [23]. In Nepal, studies have shown that community participation in forestry programs has yielded an increase in forest product output and better forest outlook, but there is dearth of studies on the financial returns of such participation at the household level [20,47].…”
Section: Smallholder Tobacco Production As a Livelihood Strategymentioning
confidence: 99%
“…Ongoing deforestation, deterioration of forest resources in conjunction with loss of biodiversity and habitat fragmentation in the tropics have been a worldwide concern [16][17][18][19]. This is because on a global scale, about 1.6 billion people's livelihoods are anchored on forest resources in the rural areas which have negative effects on the environment including climate change [20]. There is therefore one critical question that keeps lingering in relation to the reliance on forest resources for poor rural households around the world:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forest resources play an important role in the livelihoods of local communities for various products. Forest function as the main source of primary and secondary income for rural household (Moe et al 2016;Langan et al, 2016;Hlaing et al, 2017;Toe et al 2017). Local communities do business in the forest with a pattern that has become a culture of society with an orientation of economic and social needs, while environmental aspects are often an obstacle due to the limited ability of local communities.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a study conducted by Hlaing et al (2017) provides information that politicians and decision makers that local residents can be considered as one of the stakeholders of conservation activities and are designed i a participatory community-based forest management (CBFM) strategy that balances the conservation and use of forest products. Forest management activities that involve many rural communities, both as managers and as forest workers, are the key to the success of forest management.…”
Section: Introductionmentioning
confidence: 99%